The quality of life and the sociocultural, economic and health characteristics of the elderly living in the amazon region - Rosa, Tábada Samantha Marques; Ribeiro, Euler Esteves; Mota, Kennya Márcia dos Santos; Nascimento, Vanusa do; Maia-Ribeiro, Ednea Aguiar; da Cruz, Ivana Beatrice Mânica (Acta Scientiarum. Health Sciences, 2019)
WHOQOL-Bref is widely used to assess quality of life. The present study estimated the prevalence of elderly people with low quality of life and the association of socio-cultural, economic and health variables. The elderly were classified as low (< 60 points) or regular/good (> 60 points). The elderly (1431) were investigated, most of the elderly were married, with low schooling, with own income and lived with their spouse or other relatives. A large part (20.8%) reported having performed some habitual physical activity, (24.7%) smoked and (7.1%) ingested high amounts of alcohol. The mean WHOQOL-Bref score was 87.9 ± 11.6 points, with 6.1% having poor quality of life and 93.9% regular/good. There was a high number of elderly people with hypertension, type 2 diabetes, cardiovascular diseases and stroke in the low quality of life group. Also, it showed a high frequency in the elderly who reported very poor/poor vision, hearing and the prevalence of hospitalizations. The results suggested that the quality of life standards assessed by the WHOQOL-Bref are similar to the Southern Brazilian regions and the cut-off point used here was reliable for detecting poor quality of life associated with chronic morbidities.